2012
DOI: 10.1100/2012/462925
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aflatoxin on Liver and Protective Effectiveness of Esterified Glucomannan in Merino Rams

Abstract: The effects of total aflatoxin (AF) given orally on liver in Merino rams were studied. In addition, this study was conducted in order to evaluate the efficacy of an esterified glucomannan (EG) for protection against aflatoxicosis. One-year-old 32 Merino rams were divided into four equal groups. The control group (C) was fed with the commercial feed. The AF group was fed with commercial feed plus 250 μg/day of total AF. The EG group was fed with commercial feed plus 2 g/day of EG. The AF + EG group was fed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…In this study, a 7.7-fold increase in the lesional score was observed in AFB 1 -exposed animals. Notably, this study constitutes the first evaluation of the effects of a subclinical, single AFB 1 exposure in mice, and the hepatic lesions observed here are consistent with those observed in other studies that used different doses or frequencies of exposure [ 21 ].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, a 7.7-fold increase in the lesional score was observed in AFB 1 -exposed animals. Notably, this study constitutes the first evaluation of the effects of a subclinical, single AFB 1 exposure in mice, and the hepatic lesions observed here are consistent with those observed in other studies that used different doses or frequencies of exposure [ 21 ].…”
Section: Discussionsupporting
confidence: 89%
“…The microscopic alterations in liver samples with lower levels were mostly in the form of congestion in the sinusoidal and central vein, hepatocytic steatosis and fatty vacuolations, vacuolar to hydrobic degenerations and haemosidrine pigments. Nearly similar histopathology alterations were previously reported in some studies for aflatoxicosis in other species as these of Colakoglu and Donmez (2012) in Rams, Smith et al (1976) in farm animals, Armbrecht et al (1970) in sheep, Miller et al (1984) in goats, Hinton et al (2003) in rat and Ortatatli et al (2005) in broilers.…”
Section: Discussionsupporting
confidence: 67%
“…The increase of liver relative weight in present study is supported by the histopathological finding which had been shown the severe inflammation in both perilobular and interlobular area, degeneration and bile duct proliferation (P<0.05) ( Table 3). The liver hepatocytes play an essential role in the detoxification of the toxin and xenobiotics (Colakoglu and Donmez, 2012). High accumulation of the toxin promotes the degeneration (Figure 1a) that is induced by the oxidative stress and impairment of cellular metabolism (Guo et al, 2013).…”
Section: Resultsmentioning
confidence: 99%